Male Social Roles and Mobility in the Early Nordic Bronze Age. A Perspective from SE Jutland - Felding, Louise; Reiter, Samantha S.; Frei, Karin M.; Vandkilde, Helle (Danish Journal of Archaeology, 2020)
This paper provides a discussion of the increasing amount of mobility data from the Early Nordic Bronze Age (Early NBA), c. 1600-1100 BCE with particular focus on NBA II and III (c. 1500-1100 BCE). As a male-oriented study, the intent is to develop current perspectives on gender roles in the Early NBA in relation to mobility. In order to achieve our aim, we conducted strontium isotope analyses and radiocarbon dating combined with an in-depth archaeological investigation of grave goods obtained from two male burials from the Vejle region, SE Jutland. To contextualise the case study results, we also conducted network analyses of male gear from burials and ritual deposits on a regional scale, which reveal differentiated roles among men in the upper social echelon. The warrior emerged as an overall identity for high-ranking males whilst differences in male weaponry interestingly suggest that a minimum of three kinds of warriors were distinguished, reflecting social roles in war and society. The results suggest that one of the individuals was local while the other might have moved. The overall aim is to demonstrate that robust results regarding gendered mobilities will depend on the combination of several methods, datasets and scales of inquiry.